Nanoscale (FeCoNiCuMn) 3O4-FeNi / rGO composite wave-absorbing material and preparation method and application thereof
By preparing nanoscale (FeCoNiCuMn)3O4-FeNi/rGO composite absorbing material, the problems of high-entropy oxide particles agglomeration and structural damage are solved, and the absorption performance is improved and the absorption bandwidth is expanded. It is suitable for absorbing coating applications.
Patent Information
- Application Number
- CN202510050625.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-13
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2045-01-13
AI Technical Summary
When preparing wave absorbing composite materials, high-entropy oxide particles are prone to agglomeration, resulting in structural damage and poor absorption performance.
Using the preparation method of nanoscale (FeCoNiCuMn) 3O4-FeNi/rGO composite absorbing material, nano high entropy oxide and graphene composite materials with uniform particle size were prepared by combining polyethylene oxide-polypropylene oxide-polyethylene oxide triblock copolymer, graphite oxide paste and metal nitrate, and using ultrasonic dispersion and vacuum heating.
The uniform refinement of high-entropy oxide particles is achieved, which avoids particle agglomeration and structural damage, improves the material's absorption capacity and absorption bandwidth, and is suitable for low-thickness, strong absorption and wide absorption bands to absorb wave coating applications.
Smart Images

Figure CN119873906A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of wave-absorbing composite materials, and in particular to a nano-scale (FeCoNiCuMn)3O4-FeNi / rGO composite wave-absorbing material and a preparation method and application thereof. Background Art
[0002] With the widespread use of electronic devices and wireless communications, electromagnetic pollution has become a serious problem, posing a huge threat to military security, the environment and human health. Therefore, it is crucial to develop lightweight, low-thickness, strong absorption, and wide absorption band absorbing materials. In recent years, research on composite materials has shifted from single electric or magnetic components to electromagnetic composite materials.
[0003] At present, the main absorbing materials that are being studied in depth are ferrites, magnetic metals, and carbon materials. Among them, high-entropy ceramic materials have attracted widespread attention due to their unique thermodynamic, magnetic, electrical, and dielectric properties. High-entropy ceramics refer to solid solutions composed of more than five components. By adjusting the elemental composition, their magnetic and dielectric properties can be changed, which will affect the absorption capacity of electromagnetic waves. Among all types of high-entropy ceramics, high-entropy oxides ((FeCoNiCuMn)3O4) are easy to prepare and have higher stability. At present, most high-entropy oxide absorbing materials are powder particles. This structure makes the loss mechanism single, the electromagnetic wave reflection path short, and is not conducive to better absorption of electromagnetic waves.
[0004] Refining the absorber particles in composite materials at the micro-nano scale is one of the effective ways to improve the absorption performance. However, in previous reports, high entropy oxides are often heat treated using traditional tube furnaces or muffle furnaces. This process requires a slow heating and cooling process. Long-term calcination at high temperatures can easily cause particle agglomeration and structural damage to alloys and carbon materials. Generally speaking, surface diffusion in the low-temperature region plays a major role during sintering, and this process can lead to coarsening. Although the decomposition temperature of graphene in carbon materials is as high as 1000°C, the decomposition temperature will decrease in an oxidizing environment, and long-term high-temperature calcination will destroy the graphene structure. Summary of the invention
[0005] The purpose of the present invention is to provide a nanoscale (FeCoNiCuMn)3O4-FeNi / rGO composite absorbing material and a preparation method and application thereof, so as to solve the problem that when the absorbing particles in the absorbing composite material are refined at the micro-nano scale, particle agglomeration and structural destruction of the alloy and carbon material are easily caused.
[0006] To achieve the above object, the present invention provides a method for preparing a nanoscale (FeCoNiCuMn)3O4-FeNi / rGO composite absorbing material, the steps of which are as follows:
[0007] S1, dissolving the polyethylene oxide-polypropylene oxide-polyethylene oxide triblock copolymer in anhydrous ethanol, adding deionized water and ethylene glycol, and stirring until completely dissolved;
[0008] S2, adding graphite oxide paste into deionized water, and ultrasonically dispersing the graphite oxide paste;
[0009] S3, adding five metal nitrates and hexamethylenetetramine to the homogeneous solution prepared in step S1, stirring until completely dissolved, and then adding the graphite oxide paste ultrasonically dispersed in step S2, mixing to obtain a precursor solution;
[0010] S4, placing the obtained precursor solution in a polytetrafluoroethylene-lined reactor, heating it to 150-200° C. and keeping it warm, cooling it naturally to room temperature after the insulation is completed, washing it and drying it to obtain a precursor powder;
[0011] S5. Place the obtained precursor powder in a Joule heating furnace, heat it to 800-1000° C. under vacuum conditions and keep it warm.
[0012] Preferably, the volume ratio of anhydrous ethanol: deionized water: ethylene glycol in S1 is 15:10:48, and the mass volume ratio of polyethylene oxide-polypropylene oxide-polyethylene oxide: anhydrous ethanol is 1:17-19.
[0013] Preferably, the concentration of graphite oxide paste in S2 is 2 mg / mL, and ultrasonic dispersion is performed for 2 hours.
[0014] Preferably, the five metal nitrates in S3 are nitrates of manganese, iron, nickel, copper and cobalt, and the mass molar ratio of polyethylene oxide-polypropylene oxide-polyethylene oxide to the five metal nitrates is 1 g:1 mmol.
[0015] Preferably, the five metal nitrates in S3 are Mn(NO3)2·4H2O, Fe(NO3)3·9H2O, Ni(NO3)2·6H2O, Cu(NO3)2·3H2O, and Co(NO3)3·6H2O.
[0016] Preferably, the mass ratio of hexamethylenetetramine:polyethylene oxide-polypropylene oxide-polyethylene oxide is 1:2-3.
[0017] Preferably, in S4, the temperature is kept at 150-200° C. for 15 hours, and after cooling to room temperature, the mixture is washed with deionized water and anhydrous ethanol, and then dried at 60-80° C. after washing.
[0018] Preferably, the vacuum condition in S5 is a vacuum degree of -0.8-0.93 MPa, the temperature is increased at a heating rate of 1000-1200°C / min, and the temperature is kept at 800-1000°C for 6 minutes.
[0019] A nano high entropy oxide (FeCoNiCuMn)3O4-FeNi / rGO composite absorbing material prepared by the preparation method of the nanoscale (FeCoNiCuMn)3O4-FeNi / rGO composite absorbing material as described above.
[0020] An application of the nanoscale (FeCoNiCuMn)3O4-FeNi / rGO composite absorbing material as described above in the preparation of absorbing coatings.
[0021] The nanoscale (FeCoNiCuMn)3O4-FeNi / rGO composite absorbing material provided by the present invention provides basic magnetic dielectric loss capacity with spinel-type high entropy compounds, increases the interface loss and magnetic loss of the material by introducing FeNi alloy, improves the conductivity of the material by loading rGO, enhances the dielectric loss, increases the multiple reflection and scattering capabilities, and can achieve the effect of synergistic effects of multiple loss mechanisms.
[0022] Therefore, the present invention provides a nanoscale (FeCoNiCuMn)3O4-FeNi / rGO composite absorbing material and a preparation method and application thereof, and its specific technical effects are as follows:
[0023] (1) The (FeCoNiCuMn)3O4-FeNi / rGO composite absorbing material prepared by the preparation method provided by the present invention has a complete graphene structure and uniform oxide particle size, the particle size of which is between 50nm and 300nm, which effectively avoids abnormal growth of oxide grains / coarsening of oxide particles;
[0024] (2) The (FeCoNiCuMn)3O4-FeNi / rGO composite absorbing material prepared by the preparation method provided by the present invention has the advantages of low thickness, strong absorbing ability and absorption bandwidth. The thickness is 2 mm, the electromagnetic wave loss is -40.6 dB, and the absorption bandwidth is 5.4 GHz, which can meet the application requirements of the absorbing coating;
[0025] (3) The preparation method provided by the present invention is simpler, easier to operate, and suitable for large-scale production; it can provide a new idea for further improving the absorbing performance of absorbing materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings required for use in the description of the embodiments of the present invention will be briefly introduced below. Obviously, the accompanying drawings in the following description are only some embodiments of the present invention. For ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without paying creative labor.
[0027] Figure 1is an X-ray diffraction pattern of the nanoscale (FeCoNiCuMn)3O4-FeNi / rGO composite absorbing material prepared in Example 1 of the present invention;
[0028] Figure 2 is a SEM image of the nanoscale (FeCoNiCuMn)3O4-FeNi / rGO composite absorbing material prepared in Example 1 of the present invention;
[0029] Figure 3 3D reflection loss schematic diagram of the nanoscale (FeCoNiCuMn)3O4-FeNi / rGO composite absorbing material prepared in Example 1 of the present invention;
[0030] Figure 4 is an X-ray diffraction pattern of the nanoscale (FeCoNiCuMn)3O4-FeNi / rGO composite absorbing material prepared in Example 2 of the present invention;
[0031] Figure 5 is a SEM image of the nanoscale (FeCoNiCuMn)3O4-FeNi / rGO composite absorbing material prepared in Example 2 of the present invention;
[0032] Figure 6 Schematic diagram of 3D reflection loss of the nanoscale (FeCoNiCuMn)3O4-FeNi / rGO composite absorbing material prepared in Example 2 of the present invention. DETAILED DESCRIPTION
[0033] The technical solution of the present invention is further described below through the accompanying drawings and embodiments.
[0034] In order to make the purpose, technical scheme and advantages of the present application clearer, more thorough and more complete, the technical scheme of the present invention is clearly and completely described below through the accompanying drawings and examples. The following detailed descriptions are all descriptions of the embodiments, and are intended to provide further detailed descriptions of the present invention. Unless otherwise specified, all technical terms used in the present invention have the same meaning as those generally understood by those skilled in the art to which the present application belongs.
[0035] The instruments, equipment, reagents and materials used in the examples were all obtained through commercial channels.
[0036] Embodiment 1
[0037] A nanoscale (FeCoNiCuMn)3O4-FeNi / rGO composite absorbing material is prepared, and the specific steps are as follows:
[0038] S11, accurately weigh 0.6g polyethylene oxide-polypropylene oxide-polyethylene oxide (P123) and dissolve it in 11.25mL anhydrous ethanol, then add 5.1mL deionized water and 36mL ethylene glycol, stir until completely dissolved, then add 150.6mg Mn(NO3)2·4H2O (0.6mmol), 242.4mg Fe(NO3)3·9H2O (0.6mmol), 174.9mg Ni(NO3)2·6H2O (0.6mmol), 144.9mg Cu(NO3)2·3H2O (0.6mmol), 174.6mg Co(NO3)3·6H2O (0.6mmol), 0.21g hexamethylenetetramine, stir until completely dissolved. Then add 2.4mL graphite oxide paste dispersion (ultrasonic dispersion for 2h, concentration is 2mg / mL).
[0039] S12. Add the solution obtained in step S11 into a 100 mL polytetrafluoroethylene-lined reactor, keep the temperature at 170°C for 15 hours, cool naturally after the temperature is maintained, and after cooling to room temperature, wash alternately with deionized water and anhydrous ethanol until the liquid is clear, and then dry at 60°C to obtain a precursor powder.
[0040] S13, placing the obtained precursor powder in a Joule heating furnace, maintaining the vacuum degree in the furnace at -0.9 MPa, heating to 900°C at a heating rate of 1000°C / min, and keeping the temperature for 6 minutes to obtain a nano (FeCoNiCuMn)3O4-FeNi / rGO composite absorbing material.
[0041] The obtained nanoscale (FeCoNiCuMn)3O4-FeNi / rGO composite absorber was subjected to X-ray diffraction phase analysis. Figure 1 As shown in the figure, the five characteristic peaks at 30.1°, 35.2°, 42.9°, 56.8°, and 62.4° correspond to the (220), (311), (400), (511), and (440) crystal planes of the spinel structure (PDF#13-0162). The other phases were identified as FeNi alloy phases, with diffraction peaks at 44.1°, 51.4°, and 75.7°, corresponding to the (111), (200), and (220) crystal planes of the FeNi alloy (PDF#38-0419). The broad rGO diffraction peak at 23.5° of (FeCoNiCuMn)3O4 is not obvious in the spectrum, which may be due to the high intensity of the alloy diffraction peak and the low rGO composition ratio.
[0042] The obtained nanoscale (FeCoNiCuMn)3O4-FeNi / rGO composite absorber was observed by SEM. Figure 2As shown, the flaky material is graphene, and the white particles distributed thereon are high entropy oxide and FeNi alloy particles, with an average particle size of 50nm-300nm.
[0043] Use a vector network analyzer to test the electromagnetic parameters of the material, then calculate the material reflection loss according to the transmission line theory, and then use Origin software to draw the graph. The results are as follows: Figure 3 As shown, it is observed that the minimum reflection loss is -40.6dB at 2.4mm and 9.8GHz, and the effective absorption bandwidth is 5.4GHz at 1.68mm. It has stronger reflection loss and wider effective bandwidth near the low thickness of 2mm, which meets the requirements of low thickness, strong absorption and wide absorption band.
[0044] Depend on Figures 1 to 3 It can be seen that the nanoscale (FeCoNiCuMn)3O4-FeNi / rGO composite absorbing material was successfully prepared.
[0045] Embodiment 2
[0046] A nanoscale (FeCoNiCuMn)3O4-FeNi / rGO composite absorbing material is prepared, and the specific steps are as follows:
[0047] S21, accurately weigh 0.6g P123 and dissolve it in 11.25mL anhydrous ethanol, add 4.5mL deionized water and 36mL ethylene glycol, then add 147.05mg Mn(CH3COO)2·4H2O (0.6mmol), 114.56mg Fe(OH)(CH3COO)2 (0.6mmol), 149.45g (CH3COO)2Co·4H2O (0.6mmol), 149.38mg Ni(CH3COO)2·4H2O (0.6mmol), 119.79mg Cu(CH3COO)2·H2O (0.6mmol) and 0.21g hexamethylenetetramine, stir until completely dissolved. Then add 3mL graphite oxide paste dispersion (sonicated for 2h, concentration is 2mg / mL).
[0048] S22. Add the solution obtained in step S21 into a 100 mL reactor, keep it at 170°C for 15 hours, cool it naturally after the insulation is completed, and after cooling to room temperature, wash it alternately with deionized water and anhydrous ethanol several times until the liquid is clear, and then dry it at 60°C to obtain a precursor powder.
[0049] S23. Place the obtained precursor powder in a Joule heating furnace, maintain the vacuum degree in the furnace at -0.9 MPa, heat to 900°C at a heating rate of 1000°C / min, and keep warm for 6 minutes to obtain a nanoscale (FeCoNiCuMn)3O4-FeNi / rGO composite absorbing material.
[0050] The obtained nanoscale (FeCoNiCuMn)3O4-FeNi / rGO composite absorber was subjected to X-ray diffraction phase analysis. Figure 4 As shown in the figure, the five characteristic peaks at 30.1°, 35.2°, 42.9°, 56.8°, and 62.4° correspond to the (220), (311), (400), (511), and (440) crystal planes of the spinel structure (PDF#13-0162). The other phases were identified as FeNi alloy phases, with diffraction peaks at 44.1°, 51.4°, and 75.7°, corresponding to the (111), (200), and (220) crystal planes of the FeNi alloy (PDF#38-0419). The broad rGO diffraction peak at 23.5° of (FeCoNiCuMn)3O4 is not obvious in the spectrum, which may be due to the high intensity of the alloy diffraction peak and the low rGO composition ratio.
[0051] The obtained nanoscale (FeCoNiCuMn)3O4-FeNi / rGO composite absorber was observed by SEM. Figure 5 As shown, the flake material is graphene, and the white particles distributed thereon are oxide particles and alloy particles, which are distributed on the surface and side edges of the graphene.
[0052] Use a vector network analyzer to test the electromagnetic parameters of the material, then calculate the material reflection loss according to the transmission line theory, and then use Origin software to draw the graph. The results are as follows: Figure 6 As shown, it is observed that the minimum reflection loss is -57.9dB at 1.64mm and 14.6GHz, and the effective absorption bandwidth is 5.3GHz at 1.58mm. It has strong reflection loss and wide effective bandwidth near the low thickness of 1.6mm, which meets the requirements of low thickness, strong absorption and wide absorption band.
[0053] Depend on Figures 4 to 6 It can be seen that the nanoscale (FeCoNiCuMn)3O4-FeNi / rGO composite absorbing material was successfully prepared.
[0054] Therefore, the (FeCoNiCuMn)3O4-FeN i / rGO composite absorbing material prepared by the preparation method provided by the present invention has a complete graphene structure, uniform oxide particle size, and the particle size is between 50nm-300nm, which effectively avoids abnormal growth of oxide grains / coarsening of oxide particles; at the same time, it has the advantages of low thickness, strong absorbing ability, and absorption bandwidth, with a thickness of 2mm, an electromagnetic wave loss of -40.6dB, and an absorption bandwidth of 5.4GHz, which can meet the application requirements of the absorbing coating; the preparation method is simpler, easy to operate, and suitable for large-scale production; and can provide new ideas for further improving the absorbing performance of absorbing materials.
[0055] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that they can still modify or replace the technical solution of the present invention with equivalents, and these modifications or equivalent replacements cannot cause the modified technical solution to deviate from the spirit and scope of the technical solution of the present invention.
Claims
1. A method for preparing a nanoscale (FeCoNiCuMn)3O4-FeNi / rGO composite absorbing material, characterized in that: Here are the steps: S1, dissolving the polyethylene oxide-polypropylene oxide-polyethylene oxide triblock copolymer in anhydrous ethanol, adding deionized water and ethylene glycol, and stirring until completely dissolved; S2, adding graphite oxide paste into deionized water, and ultrasonically dispersing the graphite oxide paste; S3, adding five metal nitrates and hexamethylenetetramine to the homogeneous solution prepared in step S1, stirring until completely dissolved, and then adding the graphite oxide paste ultrasonically dispersed in step S2, mixing to obtain a precursor solution; S4, placing the obtained precursor solution in a polytetrafluoroethylene-lined reactor, heating it to 150-200° C. and keeping it warm, cooling it naturally to room temperature after the insulation is completed, washing it and drying it to obtain a precursor powder; S5. Place the obtained precursor powder in a Joule heating furnace, heat it to 800-1000° C. under vacuum conditions and keep it warm.
2. The method for preparing a nanoscale (FeCoNiCuMn)3O4-FeNi / rGO composite absorbing material according to claim 1, characterized in that: The volume ratio of anhydrous ethanol: deionized water: ethylene glycol in S1 is 15:10:48, and the mass volume ratio of polyethylene oxide-polypropylene oxide-polyethylene oxide: anhydrous ethanol is 1:17-19.
3. The method for preparing a nanoscale (FeCoNiCuMn)3O4-FeNi / rGO composite absorbing material according to claim 1, characterized in that: The concentration of graphite oxide paste in S2 was 2 mg / mL, and ultrasonic dispersion was performed for 2 h.
4. The method for preparing a nanoscale (FeCoNiCuMn)3O4-FeNi / rGO composite absorbing material according to claim 1, characterized in that: The five metal nitrates in S3 are nitrates of manganese, iron, nickel, copper and cobalt, and the mass molar ratio of polyethylene oxide-polypropylene oxide-polyethylene oxide to the five metal nitrates is 1g:1mmol.
5. The method for preparing a nanoscale (FeCoNiCuMn)3O4-FeNi / rGO composite absorbing material according to claim 4, characterized in that: The five metal nitrates in S3 are Mn(NO3)2·4H2O, Fe(NO3)3·9H2O, Ni(NO3)2·6H2O, Cu(NO3)2·3H2O, and Co(NO3)3·6H2O.
6. The method for preparing a nanoscale (FeCoNiCuMn)3O4-FeNi / rGO composite absorbing material according to claim 1, characterized in that the mass ratio of hexamethylenetetramine: polyethylene oxide-polypropylene oxide-polyethylene oxide is 1:2-3.
7. The method for preparing a nanoscale (FeCoNiCuMn)3O4-FeNi / rGO composite absorbing material according to claim 1, characterized in that: In S4, the mixture is kept at 150-200°C for 15 hours, cooled to room temperature, washed with deionized water and anhydrous ethanol, and dried at 60-80°C after washing.
8. The method for preparing a nanoscale (FeCoNiCuMn)3O4-FeNi / rGO composite absorbing material according to claim 1, characterized in that: The vacuum condition in S5 is -0.8-0.93MPa, and the temperature is increased at a heating rate of 1000-1200°C / min. After the temperature reaches 800-1000°C, it is kept warm for 6 minutes.
9. A nano high entropy oxide (FeCo NiCuMn) 3O4-FeNi / rGO composite absorbing material prepared by the method for preparing a nanoscale (FeCoNiCuMn) 3O4-FeNi / rGO composite absorbing material as described in any one of claims 1 to 8.
10. Use of the nanoscale (FeCoNiCuMn)3O4-FeNi / rGO composite absorbing material as claimed in claim 9 in the preparation of absorbing coatings.
Citation Information
Patent Citations
Preparation method of high-entropy alloy / oxide composite nanometer wave-absorbing material
CN109762519A
Self-supporting high-entropy oxide / graphene composite material as well as preparation method and application thereof
CN115911299A
Method for preparing high-entropy ferrite / porous carbon composite fiber electromagnetic wave absorbing sponge
CN116516527A
High-entropy alloy composite material and Joule thermal preparation method and application thereof
CN118186463A
High-entropy oxide-high-entropy alloy heterogeneous wave-absorbing material as well as preparation method and application thereof
CN118272997A
Cited By
Double-magnetic metal-carbon nano composite wave-absorbing material and preparation method thereof
CN122302822A